A COMPARISON OF NEUTROPHIL LYMPHOCYTE RATIO (NLR) BEFORE AND AFTER ANTI TUBERCULOSIS TREATMENT BASED ON AGE AND SEX CHARACTERISTICS - Azmi, Annisa Nurul; Hediningsih, Yekti; Marfu’ati, Nanik (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Indonesia is ranked third in the world with the most Tuberculosis (TB) cases. TB is an infection caused by bacteria thus can cause an inflammatory response then affects Neutrophil Lymphocyte Ratio (NLR). Anti-tuberculosis treatment with bactericidal and sterilization principles is expected to kill TB germs and reduce NLR values. The aim of this study was to analyze the NLR values in tuberculosis patients before and after anti-tuberculosis treatment based on age and sex characteristics. This is an analytic observational study using retrospective cohort approach in patients diagnosed with TB at the Muhammadiyah Kendal Hospital during January - August 2022. 70 samples were obtained through a purposive sampling method. This research used secondary data laboratory results consist of identity and NLR values before and after anti-tuberculosis treatment then analyzed with SPSS. Research data distribution wasn't normal. Results showed there was a significant comparison which was lower NLR values after treatment (p <0.001) and a significant conversion of NLR values from abnormal to normal (p <0.001). There was no significant difference based on sex before (p = 0.758) and after (p = 0.115) treatment. No significant difference was found by age category before (p = 0.174) and after (p = 0.284) treatment. Comparison of NLR values before and after anti-tuberculosis treatment found that there was a decrease in NLR values and most of the conversions were from abnormal to normal, but there were no differences based on age or sex characteristics.